A resource‐based perspective on human capital losses, HRM investments, and organizational performance. (23rd October 2012) - Shaw, Jason D.; Park, Tae‐Youn; Kim, Eugene
<x xml:space="preserve">Abstract</x> Reversing the focus on human capital accumulations in the resource‐based literature, the authors examine the issue of human capital losses and organizational performance. They theorize that human capital losses markedly diminish the inimitability of human capital stores initially, but that the negative effects are attenuated as human capital losses increase. They argue further that these effects are more dramatic when human resource management (HRM) investments are substantial. As predicted, Study 1 shows that the human capital losses (voluntary turnover rates)‐workforce performance relationship takes the form of an attenuated negative relationship when HRM investments are high. Study 2 shows stronger curvilinear effects of voluntary turnover rates on financial performance via workforce productivity under these conditions. Implications for resource‐based theory and strategic HRM are addressed.